Komponen Kimia Minyak Atsiri yang Diisolasi dari Daun Tanaman Pucuk Merah (Syzygium myrtifolium Walp.) dan Potensi Antibakteri serta Toksisitasnya - Suryati; Thaharah Alifa Aziz Yenuuar; Shafinna Hana Fadhia; Rahmi Vika Ulia; Miftahul Melsya Salsabilla; Bustanul Arifin (Universitas Andalas, 2023)
Pucuk merah (Syzygium myrtifolium Walp.) is an ornamental plant from the Myrtaceae family. Several phytochemical tests from previous researchers reported that pucuk merah contains secondary metabolites that have benefits such as antioxidants, antibacterials, and anti-cancer. In addition, the distinctive aroma produced from pucuk merah leaves indicates the presence of essential oils whose bioactivity can be studied. Still, there has been no report on this plant's chemical components or bioactivity. Therefore, this study aims to determine the content of chemical components of pucuk merah essential oil and their bioactivity as antibacterial and toxicity. The isolation of essential oils was carried out by the hydro distillation method. The chemical components of essential oils were analyzed using the Gas Chromatography-Mass Spectrometry (GC-MS) method. GC-MS results showed the presence of 42 compounds with four main compounds, namely caryophyllene (23.45%), 3-carene (15.67%), α-terpineol (10.74%), and α-pinene (5.98%) ). Antibacterial test of pucuk merah essential oil using the disc diffusion method showed strong activity against Staphylococcus aureus and Escherichia coli with inhibition zones of 16.15 ± 2.03 and 16.13 ± 1.74 mm at 100% concentration. The results of the toxicity test of pucuk merah essential oil using the BSLT (Brine Shrimp Lethality Test) method on Artemia salina Leach shrimp larvae showed strong toxic properties with an LC50 value of 3.99 µg/mL.